Dr Ducarel and his Books: Was André Coltée Ducarel a Bibliomaniac?. (14th June 2018) - Myers, Robin
Abstract: Dr Andrew Coltée Ducarel (1713–1785) Huguenot, ecclesiastical and maritime lawyer, long-serving Lambeth librarian, antiquary and pioneer in the study of Anglo-Norman architecture, was a considerable book collector. His library was for use, not collected for the beauty of design or binding. There is no record of the purchases of his English books; but the surviving correspondence with his younger brother, James Coltée Ducarel, who returned to France, documents his assiduous hunt among Paris and Caen booksellers and private collectors on his brother's behalf for books on Norman and French history, genealogy, and architecture. His elderly, bibliophile cousin, Jean Millsonneau found him rare numismatic books. Ducarel left all his collections of books, manuscripts, prints and coins to his nephew, Gerard Gustavus Ducarel, who lost no time in dispersing the whole, including collections of correspondence with fellow scholars, in two sales by John Gerard and Messrs Sotheby.